2020
DOI: 10.1007/s11356-020-08451-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of endemic fluorosis caused by drinking water in a high-fluorine area in Ningxia, China

Abstract: Endemic fluorosis is widespread in China, especially in the arid and semi-arid areas of northwest China, where endemic fluorosis caused by consumption of drinking water high in fluorine content is very common. We analyzed data on endemic fluorosis collected in Ningxia, a typical high-fluorine area in the north of China. Fluorosis cases were identified in 539 villages in 1981, in 4449 villages in 2010, and in 3269 villages in 2017. These were located in 19 administrative counties. In 2017, a total of 1.07 milli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The aquifer is mainly constituted by the gravels and sands, loamy sands and silty clay (Li et al 2016a). Weining Plain is characterized by thick aquifers, loose structure of aquifer media, abundant recharge sources of groundwater and strong water resources bearing capacity (Li et al 2020). The thickness of the phreatic aquifer ranges from 6 to 48 m, and groundwater level depth for the phreatic aquifer is less than 5 m (Li et al 2017b).…”
Section: Hydrogeologymentioning
confidence: 99%
“…The aquifer is mainly constituted by the gravels and sands, loamy sands and silty clay (Li et al 2016a). Weining Plain is characterized by thick aquifers, loose structure of aquifer media, abundant recharge sources of groundwater and strong water resources bearing capacity (Li et al 2020). The thickness of the phreatic aquifer ranges from 6 to 48 m, and groundwater level depth for the phreatic aquifer is less than 5 m (Li et al 2017b).…”
Section: Hydrogeologymentioning
confidence: 99%
“…Taking Ningxia as an example, researchers analyzed the environmental evolution process of the reduction of surface water area and soil moisture in the Aeolian sand area of Ningxia Hui Autonomous Region from the perspective of geological history. 264 towns are ecological divided for hydrological regionalization and the results showed that the environmental water shortage in the middle and north of Ningxia is severe [16][17]. The above studies have been carried out from the overall aspects of ecology and hydrology and less from soil moisture variation in desert areas.…”
Section: Zhang Et Almentioning
confidence: 99%
“…Fluoride, an essential trace element in the human body, is also an identified cause endemic environmental health events, such as dental fluorosis and bone fluorosis (Guo et al, 2021;Li et al, 2020;Wang et al, 2021;Balcerzak, 2022). The World Health Organization lists fluoride among the top ten chemicals of public health concern and indicates that the guideline limit for fluoride in drinking water should not exceed 1.5 mg/L (Aghapour et al, 2018;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%